Dendroindication of ecoclimatic condition in forest remediation area within Northern Steppe of Ukraine - Y. I. Gritsan; V. M. Lovynska; S. A. Sytnyk; A. I. Hetmanchuk (Regulatory Mechanisms in Biosystems, 2019)
We analyzed ring width, latewood width and earlywood width of Pinus sylvestris trees under normal and flood condition in Dnipropetrovsk region, within Northern Steppe of Ukraine. Precipitation from February to August seems to be the most stable climatic factor which influenced Scots pine growth rate and caused the difference between maximum and minimum ring width in normal conditions. Meteorological conditions were mainly associated with general ring values and earlywood width, and were less associated with latewood width values. Assessment of the effect of climatic signals on tree rings’ growth process in living and dead trees and in the normal and flood condition by analyses of correlation and response function was conducted. Average annual temperatures affected the tree growth negatively in normal conditions and tree increment positively in flood conditions. Annual precipitation was correlated positively with ring width, earlywood width series in normal conditions, but negatively with these series in flood conditions.